A novel intelligent film with high stability based on chitosan/sodium alginate and coffee peel anthocyanin for monitoring minced beef freshness. (25th May 2022) - Hu, Dongsheng; Liu, Xiaogang; Qin, Yuyue; Yan, Jiatong; Yang, Qiliang
Summary: This study aimed to develop a novel pH‐sensitive intelligent film for monitoring minced beef freshness based on chitosan/sodium alginate (CS–SA) and coffee peel anthocyanin (CPA). The different CPA content effects on the internal structure, physical properties and pH sensitivity of the CS–SA films were investigated. The results showed low contents of CPA (≤2%) could be evenly distributed within the CS–SA matrix with good compatibility. The addition of CPA significantly improved the physical properties and pH sensitivity of the CS–SA films. The CS–SA film containing 2% CPA (CS–SA–CPA2) showed the best tensile strength, water vapour barrier performance and most noticeable colour change. Moreover, this film exhibited good colour stability after 120 days. The CS–SA–CPA2 film changed colour from light yellow to brown to dark brown during minced beef storage, successfully indicating freshness. Therefore, the CS–SA–CPA2 film has the potential to be a pH‐sensitive material for monitoring minced beef freshness. Abstract : A novel pH‐sensitive intelligent film was successfully developed based on chitosan/sodium alginate (CS‐SA) and coffee peel anthocyanin (CPA). The film with the best performance was selected to fabricate a pH‐sensitive intelligent visual label card to track the freshness of minced beef. The label card changed from light yellow to brown to dark brown during storage of minced beef, successfully indicating freshness.